Integrated Alternative Dispute Resolution Institutions in the Financial Services Sector: Dispute Resolution Efforts in Consumer Protection Framework - Abubakar, Lastuti; Handayani, Tri (Yustisia, 2021)
This study examines and analyzes the legal implications of strengthening the integrated Alternative Dispute Resolution Institutions in the Financial Services Sector regulations. This study applies a normative juridical approach with descriptive-analytical research specifications. The data are analyzed using qualitative juridical analysis. Results show that: an Integrated Alternative Dispute Resolution Institutions in the Financial Services Sector is a dispute resolution institution that is in accordance with the characteristics of the financial services sector as an agent of trust and prioritizes consumer protection. It is expected that consumer dispute resolution is faster, cheaper, and fairer for both Business Actors and the consumers; strengthening of regulations on integrated ADR Institutions in the Financial Services Sector aims to create independent, fair, effective, and efficient dispute resolution capable of anticipating developments in the financial services sector that are increasingly complex from a legal perspective, the use of financial technology, and products/services across financial services sectors